Joint decisions promoting student engagement in the primary foreign language classroom - Valkama, Vanessa Rebecca Sanchia (2021)
The objective of this action research project was to discover how to engage students more in the primary English foreign language classroom by including them in decision-making processes. Therefore, the research question was, “How does joint decision-making affect student engagement in the primary foreign language classroom?” In order to determine the answer, I performed a small-scale action research project as a teacher trainee, where students were allowed to choose what type of activity we did to learn a certain topic in class once every week, using a questionnaire, observation grid and teacher’s journal to collect data on their emotional and behavioural engagement. I chose to focus on emotional and behavioural engagement because in my teaching experience, I have observed first hand when a student is emotionally and behaviourally engaged, it reduces the amount of undesirable behaviour that would normally lead to disruption in the classroom and negatively impact students’ academic achievement and mental well-being. Thus, the possibility of student choice increasing emotional and behavioural student engagement would be a positive outcome of the action research for both the students and the teacher. Although there were not many notable contrasts in the data collected using all three research instruments, possibly due to the initial high engagement of the students, higher levels of participation were evident after or while student choice was taking place. The results revealed that there were more differences in behavioural engagement than students’ emotional engagement, which allowed a conclusion to be formed that involving the students in decisionmaking in the classroom may have been a reason for the increase in their engaged behaviour. A possible explanation for the increase in behavioural engagement rather than emotional engagement may be that behavioural engagement was more observable than emotional engagement, and the fact that the students were initially more highly emotionally engaged than behaviourally engaged, thus not demonstrating great changes. Overall, as an outcome of this research, I discovered that the more open and inclusive I was with my students, the more they also opened up to me, which made them more engaged. Therefore, not only did this research encourage me to gain more knowledge about the topic, but as a teacher trainee it also motivated me to develop my classroom into an increasingly engaging and student-centred environment